Charge identification of fragments produced in 16O beam interactions at 200 MeV/n and 400 MeV/n on C and C2H4 targets - Galati, G.; Boccia, V.; Alexandrov, A.; Alpat, B.; Ambrosi, G.; Argirò, S.; Barbanera, M.; Bartosik, N.; Battistoni, G.; Bisogni, M. G.; Bruni, G.; Cavanna, F.; et al. (Frontiers in Physics, 2024)
of the advantageous energy deposition culminating in the Bragg peak. However, knowledge of the dose delivered in the entrance channel is limited by the lack of data on the beam and fragmentation of the target. The FOOT experiment has been designed to measure the cross sections of the nuclear fragmentation of projectile and target with two different detectors: an electronic setup for the identification of Z ≥ 3 fragments and a nuclear emulsion spectrometer for Z ≤ 3 fragments. In this paper, we analyzed the data taken by exposing four nuclear emulsion spectrometers, with C and C 2 H 4 targets, to 200 MeV/n and 400 MeV/n oxygen beams at GSI Helmholtzzentrum f ür Schwerionenforschung (Darmstadt, Germany), and we report the charge identification of produced fragments.